(untitled) (Advancements in Homeopathic Research, 2024)
Gupta et. al. in their previous three publications(1-4) demonstrated that not only patients of chronic renal failure (CRF) can be improved by homoeopathic treatment, along with change in life style, strict diet and regimen, but also the patients of acute renal failure (ARF) can be prevented from further deterioration. Gupta et. al. published two series of 3 cases each on successful management of CRF(2,3) by homoeopathic remedies avoiding dialysis and renal transplant. The third case series is on management of acute renal failure (ARF)(4) by homoeopathic medicines. This fourth case series is on successful management of CRF patients by maintaining their serum creatinine level and eGFR within a reasonable range, preventing further deterioration and improving their quality of life for a considerable period of time. The first case in this series is of an anaemic, hypertensive, diabetic male with CKD with reduction in S. Urea and Creatinine level followed for 2 years and 9 months. The second case is of a 52-year old hypertensive female and third case is of a 71-year old hypertensive male with maintained S. Urea and Creatinine level without haemodialysis for more than 1 year. In all the 3 cases, repeated renal function test and eGFR(5) was the main parameter to assess the functional status of kidney and response to homoeopathic treatment.